Distributed Systems and Applications of Information Filtering and Retrieval DART 2012: Revised and Invited Papers - Lai, Cristian; Giuliani, Alessandro; Semeraro, Giovanni; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This volume focuses on new challenges in distributed Information Filtering and Retrieval. It collects invited chapters and extended research contributions from the special session on Information Filtering and Retrieval: Novel Distributed Systems and Applications (DART) of the 4th International Conference on Knowledge Discovery and Information Retrieval (KDIR 2012), held in Barcelona, Spain, on 4-7 October 2012. The main focus of DART was to discuss and compare suitable novel solutions based on intelligent techniques and applied to real-world applications. The chapters of this book present a comprehensive review of related works and state of the art. Authors, both practitioners and researchers, shared their results in several topics such as "Multi-Agent Systems", "Natural Language Processing", "Automatic Advertisement", "Customer Interaction Analytics", "Opinion Mining". Contributions have been careful reviewed by experts in the area, who also gave useful suggestions to improve the quality of the volume.
Context-Aware based Quality of Life Telemonitoring -- Predicate Argument Structures for Information Extraction from Dependency Representations -- An Opinion Mining Model for Generic Domains -- Facilitating Collaboration and Information Retrieval: Collaborative Traces Based SWOT Analysis and Implications -- An approach for characterizing group-based interactive environments -- A Geometric Algebra based Distributional Model to Encode Sentences Semantics -- Using an Ontology for Multimedia Content Semantics, is focused on the User Generated Content (UGC) management -- Behavioral aspects in the interaction between Wikipedia and its users.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).